Takina te Kawa: Laying theFoundation, a Research Engagement Methodology in Aotearoa (New Zealand) - Taiwhati, Marama; Toia, Rawiri; Maro, Pania Te; McRae, Hiria; McKenzie, Tabitha (The Australian Journal of Indigenous Education, 2010)
Abstract In the bi-cultural context of Aotearoa (New Zealand), engagement with stakeholders that is transparent and culturally responsive is a priority for educational research. More common research approaches in New Zealand have followed a Western euro-centric model of engagement with research participants resulting in interventions and initiatives that have not necessarily served the needs of the education sector. The authors critically analyse the researcher relationship with research participants to provide a Māori perspective to guide the engagement process as researchers enter educational communities to conduct research. Embedded with Māori ideology and knowledge, the Hei Korowaiethical research framework is a platform for insider positionality that acknowledges partnership between the researcher and the researched for the benefit of knowledge development and the educational sector.